KOMPETENCJA KOLOKACYJNA – NIEDOSTATECZNIE ROZPOZNANY KOMPONENT KOMPETENCJI LEKSYKALNEJ - Targońska, Joanna (Neofilolog, 2019)
This paper emphasizes the need to include collocational competence in the model of lexical competence. Different ways of understanding of the notion “collocation” are presented together with the existing models of lexical competence. Next, a new model of lexical competence is pro-posed, i.e. the model covering lexical competence as well. The Author presents her original concept of collocational competence and argues for its development in vocabulary extension at a foreign language class.